EVALUATION OF THE KNOWLEDGE ON COST OF ORTHOPEDIC IMPLANTS AMONG ORTHOPEDIC SURGEONS - Arliani, Gustavo Gonçalves (Acta Ortop Bras, 2016)
OBJECTIVE: To determine the knowledge of Brazilian Orthopedic Surgeons on the costs of orthopedic surgical devices used in surgical implants. METHODS: A questionnaire was applied to Brazilian Orthopedic Surgeons during the 46(th) Brazilian Congress on Orthopedics and Traumatology. RESULTS: Two hundred and one Orthopedic Surgeons completely filled out the questionnaire. The difference between the average prices estimated by the surgeons and the average prices provided by the supplier companies was 47.1%. No differences were found between the orthopedic specialists and other subspecialties on the prices indicated for specific orthopedic implants. However, differences were found among orthopedic surgeons who received visits from representatives of implant companies and those who did not receive those visits on prices indicated for shaver and radiofrequency device. Correlation was found between length of orthopedic experience and prices indicated for shaver and interference screw, and higher the experience time the lower the price indicated by Surgeons for these materials. CONCLUSION: The knowledge of Brazilian Orthopedic Surgeons on the costs of orthopedic implants is precarious. Reduction of cost of orthopedics materials depends on a more effective communication and interaction between doctors, hospitals and supplier companies with solid orientation programs and awareness for physicians about their importance in this scenario.Level of Evidence III, Cross-Sectional Study.